Analisis Pengaruh Pengeluaran Pemerintah Daerah Sektor Infrastruktur, Sektor Pertanian, Sektor Pariwisata dan Pendapatan Asli Daerah (PAD) Terhadap Pertumbuhan Ekonomi Nusa Tenggara Barat (NTB) Tahun 2011-2015 - Husriatun Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
This study aims to determine the effect of local government expenditure on agriculture, tourism, road infrastructure and local own revenues (LOR) on economic growth in province of Nusa Tenggara Barat by district/city period 2011-2015. The method is used to analyze the research data is panel data, fixed effect model by using an application help Eviews 8. The result of this research is government expenditure variable for agriculture sector has a positive and significant influence on economic growth, government expenditure for tourism sector has a negative and insignificant effect on economic growth, government expenditure for road infrastructure has a negative and insignificant effect on economic growth and local own revenues (LOR) has a positive and significant influence on economic growth.